2012
DOI: 10.1590/s0004-28032012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Trend of mortality rates for gastric cancer in Brazil and regions in the period of 30 years (1980-2009)

Abstract: CONTEXT: The most recent global estimate revealed the presence of about one million new cases of stomach cancer for the year 2008, setting itself as the fourth most common cause of cancer. OBJECTIVE: The present study aims to assess the trend of mortality from stomach cancer in Brazil according to regions between 1980 and 2009. METHODS: Data on deaths from stomach cancer were obtained from the Mortality Information System, and the demographic data, from the Brazilian Institute of Geography and Statistics. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
3
21
0
2
Order By: Relevance
“…Mortality decline has been observed with different speeds of transition in the population among all age groups (17, 32, 34, 53, 55, 61, 65, 67, 75, 86, 91, 98, 106, 114, 116, 123, 124, 145) and across specific age groups, including neonates and infants (50, 99, 117), children (35, 56), adolescents (142), and adults (73, 85, 127). In some countries – such as Spain, Japan, Mexico, and Sri Lanka – good quality vital registration allows researchers to study mortality transition over long time periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality decline has been observed with different speeds of transition in the population among all age groups (17, 32, 34, 53, 55, 61, 65, 67, 75, 86, 91, 98, 106, 114, 116, 123, 124, 145) and across specific age groups, including neonates and infants (50, 99, 117), children (35, 56), adolescents (142), and adults (73, 85, 127). In some countries – such as Spain, Japan, Mexico, and Sri Lanka – good quality vital registration allows researchers to study mortality transition over long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and socio-economic determinants, including sex, income level, education level, marital status, ethnicity, regional differences, as well as wider structural and environmental factors, can influence the transition process and lead to unequal health outcomes. In this review, we observed sex differentials in mortality over time (46, 49, 51, 73, 80, 81, 86, 94, 106, 118, 123, 132, 157); regional disparities in mortality (57, 60, 62, 72, 74, 76, 77, 85, 102, 146, 148, 172); social, economic, and mortality disparities across different ethnic groups (48, 49, 90, 98, 121, 125, 156); and climatic factors as determinants of mortality transition (115, 124, 153). …”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer patients are usually faced with a poor prognosis due to diagnosis at later stages (8,24) . In these settings, combination therapy has become an established treatment for patients with locally advanced gastric cancer, whereas the high risk of locoregional relapses has favored the inclusion of radiotherapy as a perioperative component of its comprehensive therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The studies published in this issue of ARQUIVOS de GASTROENTEROLOGIA (3,7) reflects these tendency and therefore all the efforts should be developed in better sanitary health efforts to improve health conditions and educational measures must be taken to teach, show and change alimentary habits.…”
Section: Headings -Stomach Neoplasms Epidemiologymentioning
confidence: 99%